THE DEVELOPMENT OF SYSTEMATIC KNOWLEDGE TO SUPPORT AREA-BASED EDUCATION MANAGEMENT SOUTHERN BORDER PROVINCES - Vehachart, Rungchatchadaporn; Srisakda, Venas (Journal of Social Science and Cultural, 2023)
This research aims to develop systematic knowledge to support spatial education management. Southern border provinces There are research methods: 1) in-depth interviews and meetings to study the local context in real situations from School administrators, teachers, and school committees The results of the research found that all 3 schools had good practices. Project-based learning management Proactive learning management Organizing learning using the brain as a base. 2) Analyzing the data and organizing the elements to create a set of knowledge manuals. It was found that in the information system aspect Participation of the provincial area When considering each aspect, it was found that the Sufficiency Economy Philosophy aspect had a weight of (.906), followed by the aspect of providing education for all (.845) and the aspect of participation of all sectors (.141), which had a low weight. Ultimately, there are 10 elements: 1) Pride and loyalty to the nation, religion, and monarchy 2) Developing learners in the 21st century 3) Living together in a multicultural society 4) Development of learning media 5) Reduce educational inequality 6) Access Quality education, 7) environmentally friendly quality of life, 8) education management system, 9) building morale and encouragement, and 10) integrating education with agencies at all levels, and 3) presenting systematic knowledge. Support the organization of spatial studies by using questionnaires to test in educational institutions that are not a sample of 90 people using purposive sampling methods. Data were collected using a questionnaire. to find that cooperation network Develop innovations in supporting budgets and resources for educational reform. Knowledge has an indirect effect (Indirect effect) through the knowledge system component. Knowledge has an indirect effect. through the inequality component Knowledge has an indirect effect through and management of special areas.